2016
DOI: 10.1007/s12583-016-0679-3
|View full text |Cite
|
Sign up to set email alerts
|

The tauride ophiolites of Anatolia (Turkey): A review

Abstract: The Tauride ophiolites lie on the northern and southern flanks of an E-W-trending Tauride carbonate platform. They mainly consist of three tectonic units namely in ascending order, ophiolitic mélange, sub-ophiolitic metamorphic sole and oceanic lithospheric remnants. They were generated above intra-oceanic subduction zones and emplaced over the Tauride carbonate platform from different Neotethyan oceanic basins in the Late Cretaceous. Tauride ophiolites from west to east are described and reviewed. All are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 96 publications
(203 reference statements)
1
59
0
3
Order By: Relevance
“…The petrology of isolated dykes along the Tauride belt suggests that they originated from depleted or enriched mantle sources as a result of either (a) ridge-subduction (Lytwyn & Casey, 1995;Polat et al, 1996), or (b) slab break-off (Çelik, 2007;Parlak et al, 2006), or (c) multiple intra-oceanic thrusting and emplacement in small oceanic basins (Çelik, 2007;Çelik & Chiaradia, 2008) and (d) asymmetrical ridge collapse (Dilek et al, 1999). Parlak (2016) suggested that subduction initiation and roll-back processes (Stern & Bloomer, 1992) could best explain the structural and petrological relationships of the ophiolite genesis, metamorphic sole formation and subsequent dyke emplacement along the Tauride mountain range. During subduction initiation, mainly OIB-like alkaline and MORB-type tholeiitic basalts were accreted to the base of the overriding oceanic plate and metamorphosed under amphibolite facies conditions between about 96-90 Ma ago, based on 40 Ar ages.…”
Section: Discussionmentioning
confidence: 99%
“…The petrology of isolated dykes along the Tauride belt suggests that they originated from depleted or enriched mantle sources as a result of either (a) ridge-subduction (Lytwyn & Casey, 1995;Polat et al, 1996), or (b) slab break-off (Çelik, 2007;Parlak et al, 2006), or (c) multiple intra-oceanic thrusting and emplacement in small oceanic basins (Çelik, 2007;Çelik & Chiaradia, 2008) and (d) asymmetrical ridge collapse (Dilek et al, 1999). Parlak (2016) suggested that subduction initiation and roll-back processes (Stern & Bloomer, 1992) could best explain the structural and petrological relationships of the ophiolite genesis, metamorphic sole formation and subsequent dyke emplacement along the Tauride mountain range. During subduction initiation, mainly OIB-like alkaline and MORB-type tholeiitic basalts were accreted to the base of the overriding oceanic plate and metamorphosed under amphibolite facies conditions between about 96-90 Ma ago, based on 40 Ar ages.…”
Section: Discussionmentioning
confidence: 99%
“…Crustal ages are scattered but cluster around 185–180 Ma (Dilek & Thy, ; Robertson et al, ; Uysal et al, ; Topuz et al, ), and associated metamorphic soles have slightly younger 40 Ar/ 39 Ar ages of 177.1 ± 1.0 and 166.9 ± 1.1 Ma (Çelik et al, , ; Çörtük et al, ). South of the Izmir‐Ankara suture, Upper Cretaceous ophiolites occur scattered above the Anatolide‐Tauride belt (e.g., Maffione et al, ; Parlak, ; Robertson, ; Robertson et al, ) (Figure ). No Jurassic ophiolites have been found underlying the Cretaceous ophiolites in Turkey and were thus not obducted onto Greater Adria prior to the Cretaceous.…”
Section: Geological Setting and The Concept Of The Neo‐tethys Oceanmentioning
confidence: 99%
“…The overall IBM forearc architecture as inferred from this study matches distinct structural features in ophiolites worldwide, especially those formed in a SSZ setting. SSZ ophiolites include the Tethyan ophiolites of the Alpine-Mediterranean region (Beccaluva et al, 2004;Parlak, 2016;Robertson et al, 2002), the Cordilleran and western Pacific ophiolite complexes (Hopson et al, 2008;Robertson, 1989;Shervais et al, 2004;Snow & Shervais, 2015), and the Ordovician Appalachian-Caledonian ophiolites (e.g., Bedard et al, 1998;Cawood & Suhr, 1992;Dewey & Casey, 2011;Jenner et al, 1991).…”
Section: Impacts On Ssz Ophiolite Analoguesmentioning
confidence: 99%